Études pour piano - Dusapin, Pascal 1955-; Dusapin, Pascal 1955- (Musicales, 2012)
This CD-Book is composed of Pascal Dusapin's studies for piano performed by the pianist Vanessa Wagner, photography by the composer as well as a text by Michel Onfray. The aim is to create an all-encompassing work expressing the close relationship between the artist's musical production and his photography